First of all, move all terms to the same side:
![x^3 + 3x^2 - 8 x = 0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8gn5wkbqeggoulsd4d7y7h0exis591c6zm.png)
You can factor an x, which means that
is a solution:
![x(x^2+3x-8)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/pqgl4hncm5vgq9walbtvee31fypy5wx3ww.png)
This expression is further factorizable if the quadratic equation has any solution. Using the quadratic formula, we can find that they are
So, we have
![x(x^2+3x+8) = 0 = \iff x = 0,\quad x =-(3 + √(41))/(2) ,\quad x =-(3 - √(41))/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cp4pfrk6u2pui4vv2z0r65oaakaef7mynz.png)